Strategies preventing contrast-induced nephropathy after coronary angiography: a comprehensive meta-analysis and systematic review of 125 randomized controlled trials - Ali-Hasan-Al-Saegh, Sadeq; Weymann, Alexander (Angiology, 2017)
This systematic review with meta-analysis sought to determine the strength of evidence for the effects of hydration (sodium bicarbonate [SB] and normal saline [NS]), supplementations ( N-acetylcysteine [NAC] and vitamin C), and some common drugs (adenosine antagonists [AAs], statins, loop diuretics, and angiotensin-converting enzyme inhibitors [ACEIs]) on the incidence of contrast-induced nephropathy (CIN) and requirement for hemodialysis after coronary angiography. After screening, a total of 125 trials that reported outcomes were identified. Pooled analysis indicated beneficial effects of SB versus NS (odds ratio [OR] = 0.73; 95% confidence interval [CI]: 0.56-0.94; P = .01), NAC (OR = 0.79; 95% CI: 0.70-0.88; P = .001), vitamin C (OR = 0.64; 95% CI: 0.45-0.89; P = .01), statins (OR = 0.45; 95% CI: 0.35-0.57; P = .001), AA (OR = 0.28; 95% CI: 0.14-0.47; P = .001), loop diuretics (OR = 0.97; 95% CI: 0.33-2.85; P = .9), and ACEI (OR = 1.06; 95% CI: 0.69-1.61; P = .8). Overall, hydration with SB, use of supplements, such as NAC and vitamin C, and administration of statins and AA should always be considered for the prevention of CIN after coronary angiography.